Understanding the work-life balance of female faculty members with young children in a state university - Rivera, Kimberly; Isabel P. Martin (ILIN Institute Makassar, 2025)
This research investigated how university teacher-mothers with young children balance their professional and maternal roles. Using narrative analysis and thematic inquiry, the research investigated the challenge, coping mechanisms, and institutional support mechanisms required by five purposively chosen teacher-mothers from various campuses of a state university. Findings indicated that teacher-mothers experience perpetual challenges, including pressure from regular teaching, administrative tasks, research tasks, and extension and production activities. Balancing these roles with motherhood was complicated and draining, often resulting in work and family life conflicts. Coping mechanisms involved preparing lessons in advance, prioritizing childcare over work when needed, seeking assistance from family and community members, and strictly following official working hours to maintain clear boundaries. Participants emphasized the imperative need for institutional support, including an on-campus childcare facility and clear-cut policies for flexible working hours. These mechanisms would make it easy to find reliable childcare and offer much-needed flexibility to adjust to the unpredictable demands of caring for young children. This research surmises the need to develop family-friendly policies in academic institutions to develop a more inclusive and supportive environment for female faculty members. By recognizing their dual roles as educators and mothers, universities can achieve work-life balance and improve faculty well-being and productivity.